2015
DOI: 10.1182/blood-2014-12-616961
|View full text |Cite
|
Sign up to set email alerts
|

Central nervous system relapse in peripheral T-cell lymphomas: a Swedish Lymphoma Registry study

Abstract: Key Points• CNS involvement at relapse/ progression in PTCL occurred at a frequency similar to what is seen in aggressive B-cell lymphomas.• Outcome after relapse is generally very poor in patients with PTCL and is not significantly altered by presence of CNS involvement at relapse.Central nervous system (CNS) relapse in non-Hodgkin lymphoma (NHL) carries a very poor prognosis. Risk factors and outcome have been studied in aggressive B-cell lymphomas, but very little is known about the risk in peripheral T-cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
45
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 25 publications
5
45
2
1
Order By: Relevance
“…The rate of CNS involvement in this population was as high as 33%, supporting the argument for primary CNS prophylaxis at the time of diagnosis. Despite higher rates of CNS dissemination compared to previously reported incidence in other mature T-cell lymphomas (4.5%) [21], mortality is primarily due to uncontrolled systemic disease. Flow cytometry showed a CD4+/CD8-, CD25+ CD7- T-cell population in most patients, reflecting the typical ATLL immunophenotype.…”
Section: Discussionmentioning
confidence: 78%
“…The rate of CNS involvement in this population was as high as 33%, supporting the argument for primary CNS prophylaxis at the time of diagnosis. Despite higher rates of CNS dissemination compared to previously reported incidence in other mature T-cell lymphomas (4.5%) [21], mortality is primarily due to uncontrolled systemic disease. Flow cytometry showed a CD4+/CD8-, CD25+ CD7- T-cell population in most patients, reflecting the typical ATLL immunophenotype.…”
Section: Discussionmentioning
confidence: 78%
“…The 5-year cumulative incidence of CNS relapse was 2.1% in our study. In a study from the Swedish Lymphoma Registry, 4.5% (28/625) of patients developed CNS relapse at a median of 4.3 months after diagnosis [ 6 ]. Yi and colleagues reported an even higher incidence of CNS involvement of 8.8% (20/228) in patients with PTCL at a median time to CNS disease of 6.1 months, though they included patients who had CNS involvement at the time of diagnosis [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…The association between the site of disease involvement and future risk of CNS disease is worth evaluating. The Swedish Lymphoma Registry study identified skin and gastrointestinal tract involvement are significant risk factors for CNS relapse [ 6 ]. Yi and colleagues identified paranasal sinus involvement as a significant risk factor for CNS relapse [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ten patients (1.3 %) had CNS involvement at diagnosis, whilst 31/755 (5.0 %) developed CNS involvement at a median of 4.3 months after diagnosis. The presence of B-symptoms, multiple extranodal sites of involvement, and cutaneous involvement were independent predictors of CNS involvement [89]. Yi et al reported a crude incidence of CNS of 8.8 % in 228 patients with nodal PTCL [90].…”
Section: Peripheral T Cell Lymphomamentioning
confidence: 98%